2017
DOI: 10.1038/s41598-017-05658-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of aromatase expression in the anterior amygdala of the developing mouse brain depends on ERβ and sex chromosome complement

Abstract: During development sex differences in aromatase expression in limbic regions of mouse brain depend on sex chromosome factors. Genes on the sex chromosomes may affect the hormonal regulation of aromatase expression and this study was undertaken to explore that possibility. Male E15 anterior amygdala neuronal cultures expressed higher levels of aromatase (mRNA and protein) than female cultures. Furthermore, treatment with oestradiol (E2) or dihydrotestosterone (DHT) increased Cyp19a1 expression and aromatase pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 51 publications
5
21
0
Order By: Relevance
“…It was found that selective agonists for ERα or for the membrane ER GPR30 are not able to reproduce the effect of E 2 on aromatase mRNA. However, a selective ERβ agonist fully reproduced the effect of E 2 and DHT on aromatase expression . In concordance with a possible ERβ involvement in aromatase regulation by E 2 or DHT, a selective antagonist for ERβ in combination with E 2 or DHT prevented the hormonal effects …”
Section: Aromatasesupporting
confidence: 64%
See 3 more Smart Citations
“…It was found that selective agonists for ERα or for the membrane ER GPR30 are not able to reproduce the effect of E 2 on aromatase mRNA. However, a selective ERβ agonist fully reproduced the effect of E 2 and DHT on aromatase expression . In concordance with a possible ERβ involvement in aromatase regulation by E 2 or DHT, a selective antagonist for ERβ in combination with E 2 or DHT prevented the hormonal effects …”
Section: Aromatasesupporting
confidence: 64%
“…47 Surprisingly, 3β-diol treatment increased aromatase expression in neuronal cultures derived from the amygdala of female FCG mice. 48 These findings could shed light on our previous results of hormonal regulation in neuronal cultures. Because aromatase mRNA expression was regulated by both E 2 and DHT and the magnitude of this effect was almost equivalent, 22 we can hypothesise that E 2 and 3β-diol bind to ERβ to regulate aromatase expression in amygdala neurones of the developing mouse brain.…”
Section: Aromatasesupporting
confidence: 54%
See 2 more Smart Citations
“…The interaction between the sex chromosome complement and gonadal hormones also determines the expression of aromatase and estrogen receptors (Cisternas et al, 2015(Cisternas et al, , 2017Cambiasso et al, 2017) in the brain and, therefore, may contribute to the different effects of estrogen therapy in males and females. However, this possibility needs to be experimentally explored.…”
Section: Sex Chromosome Effects In the Neuroprotective Actions Of Estmentioning
confidence: 99%